The Role of Accounting in Developing MSMEs in the Era of Globalization - Dito Aditia Darma Nasution; Renny Maisyarah; Fildzah Shabrina; Rimba Simanjuntak; Ancer Martati Ndraha; Heny Nurlaili; M.Diaz Arasta (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze the role of accounting in developing Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, especially in facing the challenges of globalization. In the era of increasingly competitive globalization, MSMEs are required to have a good financial management system in order to survive and develop. Accounting serves as a tool to monitor and manage finances, make strategic decisions, and improve competitiveness. However, many MSMEs still face various obstacles, such as limited accounting knowledge, human resources, and access to technology. This study uses a qualitative descriptive approach with in-depth interviews and document analysis to collect data. The results of the study show that although most MSME actors recognize the importance of accounting in financial management, only a small number have applied it systematically. The main factors hindering the effective implementation of accounting are limited knowledge of accounting, the cost of accounting software, and a lack of adequate training. However, MSMEs that successfully implement accounting well, both manually and technology-based, show improvements in terms of operational efficiency and access to financing. This study suggests the importance of accounting training for MSME actors and support from the government and related institutions to strengthen the accounting capacity of MSMEs so that they can compete in the global market. In addition, the implementation of more affordable accounting technology can also help MSMEs to be more efficient in managing their finances.